Demonstrating managed aquifer recharge as a solution for climate change adaptation: results from Gabardine project and asemwaterNet coordination action in the Algarve region (Portugal) - Lobo Ferreira, J. P. C. (2014)
In the Algarve southern Portugal region, Managed Aquifer Recharge (MAR) research activities have been developed to provide not only water surplus storage in aquifers during wet years, focusing in the Querença-Silves aquifer (FP6 ASEMWATERNet Coordination Action), but also groundwater quality rehabilitation in the Campina de Faro aquifer (FP6 Gabardine Project). Following MAR research potentialities in southern Portugal, this paper describes the objectives, conceptual demonstration, background and capabilities of one of the selected Circum-Mediterranean pilot sites (in Portugal) that will be researched in the new FP7-ENV-2013-WATER-INNO-DEMO MARSOL project, which started Dec. 1st, 2013. In the Algarve pilot site, several case-study areas will be located in the Querença-Silves aquifer and in the Campina de Faro aquifer